Medication errors and adverse drug events in peri-operative pediatric anesthetic care over twenty years: a retrospective observational study - Shemila Abbasi; Muhammad Azhar Sharafat; Fauzia Khan (BMC Anesthesiology)
Abstract Background Children are at an increased risk of medication errors (MEs) during perioperative care compared to adult patients. This study aimed to critically look at medication errors and determine the frequency of adverse drug events and corrective measures taken for medication errors reported over 20 years in pediatric anesthetic care in the anesthesia department of a tertiary care teaching institution in a lower middle-income country (LMIC). Methods Two investigators conducted a retrospective review of all critical incident forms received between January 2001 and December 2020 and identified medication errors related to patients aged 18 years or less. In the second phase of the audit, these medication errors were assessed in detail and adverse drug events were identified using a standardized protocol. We also analyzed the strategies that were employed to prevent such incidents in the future. Results One hundred and ninety-six pediatric medication errors were identified. 40% of errors were reported in children between 13 and 72 months of age and 58% at induction. The majority of events took place during administration, preparation, and dispensing i.e., 45%, 41%, and 6% respectively. The adverse drug events occurred in 27 (1.2%) reports and life-threatening events in only one report. Conclusion 13% of the medication errors progressed to adverse drug events (ADE) and half of those were serious and life-threatening. Reinforcement of standard practice in departmental critical incident meetings, patient safety workshops and lessons to learn e-mails were some low-cost strategies to enhance medication safety during anesthesia.